2016
DOI: 10.1186/s13073-016-0326-8
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing diagnostics of bacteremia in septic patients

Abstract: BackgroundBloodstream infections remain one of the major challenges in intensive care units, leading to sepsis or even septic shock in many cases. Due to the lack of timely diagnostic approaches with sufficient sensitivity, mortality rates of sepsis are still unacceptably high. However a prompt diagnosis of the causative microorganism is critical to significantly improve outcome of bloodstream infections. Although various targeted molecular tests for blood samples are available, time-consuming blood culture-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
281
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 292 publications
(289 citation statements)
references
References 53 publications
4
281
1
3
Order By: Relevance
“…It is unknown whether these bacterial organisms were actually present within the patient or alternatively their nucleic acids were introduced via laboratory reagents (51) or were sample carryover from a prior sequencing run. However, some of the detected bacteria such as Propionibacterium , a common skin inhabitant, or Ralstonia have been shown before to be present in human blood (52,53). The contig-based taxonomy analyses also clearly showed Ebola virus to be present, and confirmed that many contigs belonged to the same bacterial groups identified by read-based analyses.…”
Section: Resultsmentioning
confidence: 99%
“…It is unknown whether these bacterial organisms were actually present within the patient or alternatively their nucleic acids were introduced via laboratory reagents (51) or were sample carryover from a prior sequencing run. However, some of the detected bacteria such as Propionibacterium , a common skin inhabitant, or Ralstonia have been shown before to be present in human blood (52,53). The contig-based taxonomy analyses also clearly showed Ebola virus to be present, and confirmed that many contigs belonged to the same bacterial groups identified by read-based analyses.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study used sequence-based metagenomics to detect free-circulating DNA from plasma samples of septic patients [86]. The authors analysed 62 samples from seven sepsis patients, six patients who underwent abdominal surgery and 12 healthy volunteers at different time points.…”
Section: Translational Metagenomics In Clinical Diagnosticsmentioning
confidence: 99%
“…Discrimination between infection and colonization is made possible by calculating the Sepsis Indicating Quantifier (SIQ) score [98]. Analogous to PCR-based techniques, a further advantage of NGS is the prediction of particular resistance phenotypes [98]. NGS will become increasingly interesting in the future, since with this method-analogous to blood cultures-there exists the possibility of a widescale search for the pathogen which is independent of the pathogen growth rate.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…In this method, cellfree DNA (cfDNA) is extracted from plasma samples, and all pathogens are detected and sequenced. Discrimination between infection and colonization is made possible by calculating the Sepsis Indicating Quantifier (SIQ) score [98]. Analogous to PCR-based techniques, a further advantage of NGS is the prediction of particular resistance phenotypes [98].…”
Section: Next-generation Sequencingmentioning
confidence: 99%